Jamus Kalimasada Leather Craft in Urban Javanese Culture - Lutfianto Lutfianto; Abdul Munip; Maharsi Maharsi (Institut Seni Indonesia Yogyakarta, 2026)
This article examines Jamus Kalimasada leather craft as a form of visual communication within Javanese urban cultural practice. Traditionally recognized in wayang narratives as a sacred heirloom, Jamus Kalimasada is reinterpreted through buffalo hide craft employing tatah and sungging techniques combined with Islamic calligraphy and ornamental motifs. This study aims to analyze the visual construction, material processes, and symbolic meanings through which tauhid is articulated in contemporary craft practice. The research applies a qualitative descriptive method using visual observation, documentation, and semi-structured interviews with the artisan. The collected data were analyzed through visual and thematic interpretation focusing on composition, ornamentation, and symbolic configuration. The findings show that the integration of shahada calligraphy, gunungan symbolism, and geometric ornamentation creates a structured visual articulation of tauhid that functions beyond decorative purposes. The hierarchical arrangement of visual elements communicates religious meaning through materiality, form, and compositional order rather than verbal doctrine. In the context of urban society, the craft operates as a medium of cultural negotiation that preserves local religious identity while responding to modernization, commercialization, and the dominance of instant visual culture. This study contributes to the discourse on urban society’s arts by positioning traditional buffalo hide craft as a communicative and social practice capable of sustaining Islamic-Javanese symbolism and cultural continuity within contemporary urban environments.